KONFLIK GENDER NOVEL NAMAKU HIROKO KARYA NH. DINI - Jayanti, Heni Dwi; Nasution, Ismail; Helda, Trisna (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by gender conflict and the problematict of the life of a woman named Hiroko who comes from a poor family who is always bullied and harassed when pitted fate of her dignity as a housemaid in the city. The focus of this research in the form of the question is " how gender conflicts novel Nh My name is Hiroko works. Dini, which includes the forms of gender conflict, gender conflict causes, and consequences of gender conflict ? ". The purpose of this study is to describe and explain the forms of gender conflict, gender conflict causes and consequences of gender conflict.                                                                                This research is a qualitative study using descriptive methods. The data in this study are the elements (such as text) that supports gender conflict. Data source is the novel My Name Hiroko works Nh. Dini. Stages of the research done by: (1) to read the novel, (2) identify the text (notes) (3) inventory data used in the study ), (4) Classifying data related to gender conflict. Data analysis of this study showed that female characters (Hiroko) gender conflict; (1) marginalization (economic impoverishment ), (2) Subordinated ( position does not matter ), (3) stereotypes ( negative marking),  (4) violence (5) workload. causes of gender conflict is caused by several factors, namely economic factors, educational factors, social factors, and cultural factors. gender conflict is a result of physical and psychological violence against the main female characters.                                                                   Suggestions in this study is expected to researchers further to explore other conflicts of the novel My name is Hiroko works Nh. Dini, is expected to readers, especially students to continue to read works of literature, teachers are expected to Indonesian literature also presents the lessons more interesting.